Teresa of Avila, the Holy Spirit, and the Place of Salvation - Brouillette, André (Paulist Press, 2021)
"An exploration of the role of the third Person of the Trinity in the works of Teresa of Avila, and its influence on pneumatology, the theological study of the Holy Spirit"--